Ecological Engineers: Southeastern Pocket Gophers Are One of Nature's Architects - Gabriel J. Miller; Steve A. Johnson; Lora L. Smith (EDIS)
WEC-244, a 4-page illustrated fact sheet by Gabriel J. Miller, Steve A. Johnson, and Lora L. Smith, explains autogenic and allogenic environmental engineering, with brief discussions of live oak trees and beavers as examples, and describes the southeastern pocket gopher’s role in Florida ecosystems as an allogenic environmental engineer. Published by the UF Department of Wildlife Ecology and Conservation, April 2008.